Gender identities and roles : the representation of women and children in South African films about HIV and AIDS - Mdege, Norita (Centre for Film and Media Studies, 2015)
This dissertation examines representations of women and children in South African films about HIV and AIDS, paying particular attention to issues relating to the advancement and empowerment of the two groups. The dissertation focuses on two films: Yesterday (Darrell Roodt, 2004) and Life Above All (Oliver Schmitz, 2010). These two films represent marginalised communities and identities. Yesterday focuses on the experiences of rural women, while Life Above All focuses on women and children living in a small town on the urban periphery. In order to contextualise the two films as well as the textual and theoretical analysis found in the body of the dissertation, the first chapter provides a brief outline of some of the concerns regarding the representations of women and children in South African films about HIV and AIDS. These concerns include the debate surrounding the authenticity of the representations of poor, black women by male, middle-class, white filmmakers, as well as the authenticity of the representations of children by adult filmmakers. Chapter 2 provides additional contextual information by defining and considering the various concepts and theories on which the study is built. These include the naturalist, humanist and pluralist methods of representing HIV/AIDS, as well as the semiotic and discursive approaches to analysing audio-visual texts. Chapter 3 consists of a close textual analysis of Yesterday. The chapter problematises representations that place too much emphasis on marginal communities‘ need for external help. It argues that the film‘s focus on generating sympathy from external viewers with the 2 hope that they might be persuaded to help women like the film‘s main character, Yesterday, hinders the promotion of empowerment. Chapter 4 critically analyses the representation of children in Life Above All, with special attention paid to self-development and agency. This chapter argues that the film neglects children‘s self-development and long-term empowerment by placing too much value on the virtues of selfless sacrifice. Chapter 5 concludes that the use of stereotypes and the prioritisation of easy to understand educational information and narratives in South African films about HIV/AIDS hinder a deeper understanding of identities as well as the promotion of women‘s and children‘s empowerment. Effective collaboration between filmmakers and the represented groups would lead to representations of identities that are more truthful to the complexities of the experiences of those infected and/or affected by HIV/AIDS. In addition, I argue that increased participation of female filmmakers would lead to more diversified representations of women‘s and children‘s identities and experiences.